Developing a Decision Support System with Dynamic Criteria for The Best Employee Assessment - Deborah Kurniawati; Dara Kusumawati; Munifatul Arifah (Journal of International Conference Proceedings (JICP), 2019)
One of the efforts of the organizations management to foster the morale of human resources (HR) is to reward the best performing HR. HR with the best performance is assessed by various criteria determined by the organization. The problem is, how can a large organization that has many branches and / or organizational fields be able to select HR with the best performance objectively; while each branch or field of organization can have different emphases or interests in each HR assessment criteria. This research develops a decision support system that can be used to select the best HR with dynamic criteria and weighting. Criteria can be added or reduced, also the weight of the criteria can be adjusted to the system user. Decision support system was developed using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. With TOPSIS it is possible to enter criteria that are expected to be positive and criteria that are expected to be negative. The results of the research conducted are a decision support system for determining the best employees with a dynamic and flexible multi model, where the criteria and weighting can be adjusted to the needs of the branch office or each part.